2016
DOI: 10.5194/tc-10-2971-2016
|View full text |Cite
|
Sign up to set email alerts
|

Active subglacial lakes and channelized water flow beneath the Kamb Ice Stream

Abstract: Abstract. We identify two previously unknown subglacial lakes beneath the stagnated trunk of the Kamb Ice Stream (KIS). Rapid fill-drain hydrologic events over several months are inferred from surface height changes measured by CryoSat-2 altimetry and indicate that the lakes are probably connected by a subglacial drainage network, whose structure is inferred from the regional hydraulic potential and probably links the lakes. The sequential fill-drain behavior of the subglacial lakes and concurrent rapid thinni… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(57 citation statements)
references
References 52 publications
(71 reference statements)
3
53
1
Order By: Relevance
“…Our results show that KT1 was the only lake of the three to exhibit dynamic behavior between 2003 and 2009, with height on the lake decreasing by 0.23 m a −1 after accounting for the 0.10 m a −1 regional thickening signal. All three lakes showed dynamic height changes during 2014, consistent with Kim and others (2016). The height changes on these lakes were abrupt: ice-surface height at KT1 and KT3 increased by 2.5 m and 1.7 m over 4 months, while the mean height of KT2 increased by 1.7 m in a single month (equivalent to >20 m a −1 ).…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…Our results show that KT1 was the only lake of the three to exhibit dynamic behavior between 2003 and 2009, with height on the lake decreasing by 0.23 m a −1 after accounting for the 0.10 m a −1 regional thickening signal. All three lakes showed dynamic height changes during 2014, consistent with Kim and others (2016). The height changes on these lakes were abrupt: ice-surface height at KT1 and KT3 increased by 2.5 m and 1.7 m over 4 months, while the mean height of KT2 increased by 1.7 m in a single month (equivalent to >20 m a −1 ).…”
Section: Resultssupporting
confidence: 90%
“…The extended record of surface-height anomalies has demonstrated that several, but not all, locations identified as active subglacial lakes continued to be active after the end of the ICESat mission in 2009. On Whillans, Kamb, MacAyeal, Institute, Thwaites, and Slessor ice streams, there were eight locations that exhibited large (>1 m) surface-height anomalies afor the period 2010–16, in addition to the 12 events previously reported using CryoSat-2 data (McMillan and others, 2013; Siegfried and others, 2014, 2016; Kim and others, 2016; Smith and others, 2017). Following existing literature (e.g.…”
Section: New Insights Into Antarctic Subglacial Hydrology From Extendmentioning
confidence: 64%
See 3 more Smart Citations